Performance evaluation and optimization of CH3NH3PbBr3 based planar perovskite solar cells using various hole-transport layers. (1st April 2022) - Jeyakumar, R.; Bag, Atanu
Highlights: Variuos hole-transport layers are used independently. Ohmic contact region is identified by tuning electrode work functions. Based on our results, an alternate to Au, low-cost contact materials are suggested. Commonly used expensive hole-transport layer can be replaced. Current density depends on reflectance from hole-transport layer. Abstract: Metal halide perovskites are promising absorber materials for solar cell applications due to (i) low-cost processing methods, and (ii) cell efficiency is comparable to the standard silicon solar cells. Methylammonium lead bromide (CH3 NH3 PbBr3 ) is a metal halide perovskite having wide band gap suitable for high open-circuit voltage ( V oc ) solar cell. Here we report the performance of CH3 NH3 PbBr3 based solar cells by using various hole-transport layers (HTLs) independently with titanium dioxide (TiO2 ) as electron transport layer (ETL). Spiro-OMeTAD was used as HTL in the control device. Absorbance study indicates the band gap of CH3 NH3 PbBr3 is around 2.25 eV. Energy band alignment shows the superior band alignment across the device when copper thiocyanate (CuSCN) is used. Short-circuit current density ( J sc ) is independent of electrode work functions. However, J sc depends upon internal reflection at the absorber/HTL interface and reflection is high for CuSCN and low for nickel oxide (NiO). Our result shows that fill factor and efficiency depends on absorber thickness, top and bottom electrode work functions. For Ohmic contact, top electrode and bottom electrode work functions must be between −4.0 eV to −4.4 eV and −4.9 eV to −5.26 eV respectively and device performs excellent in these regimes. For the control device, V oc, J sc, fill factor, and efficiency of 2.10 V, 9.64 mA/cm 2, 0.90, and 18.42% were obtained. Whereas for the cell having CuSCN as HTL, a high efficiency of 23.39% with V oc of 2.10 V, J sc of 13.04 mA/cm 2, and fill factor of 0.85 were obtained.